The opacity of international fertilizer companies: reluctance to adopt transparency and traceability systems - Semeijn, Janjaap; Van Duyse, Edwin; Lambrechts, Wim; Gelderman, Cees J. (Sustainability Letters, 2025)
With the introduction of new regulations, such as the European Corporate Sustainability Due Diligence Directive, transparency and traceability have become essential for demonstrating sustainable (supply chain) management practices. This study aims to explore the reluctance of fertilizer companies to disclose the origins of their materials, despite significant environmental, health, safety, and food quality implications of fertilizer use. To achieve this, we analysed sustainability reports to assess how these companies publicly account for their traceability and transparency efforts. Additionally, semi-structured expert interviews with high-level managers were conducted to uncover their perceptions, motivations, and their (limited) willingness to adopt comprehensive transparency and traceability systems. Our findings indicate that fertilizer companies primarily react to legislative requirements and political risks rather than proactively embracing traceability. Internal and external stakeholder perspectives diverge significantly: while some managers view existing quality systems as sufficient for ensuring product safety, others recognize traceability as a critical component of quality assurance. Few managers are willing to expand transparency unless mandated by regulation or stakeholder pressure. Perceived risks, such as potential liability and competitive disadvantage, further hinder progress toward full traceability. This study highlights the tension between regulatory demands and common business practices. For the industry, embracing traceability and transparency not only aligns with evolving regulatory requirements, but also enhances stakeholder trust and secure a competitive edge in increasingly sustainability-focused markets.